2011
DOI: 10.1007/s13311-011-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Concepts in Myeloid Cell Biology after Spinal Cord Injury

Abstract: Summary: Traumatic spinal cord injury (SCI) affects the activation, migration, and function of microglia, neutrophils and monocyte/macrophages. Because these myeloid cells can positively and negatively affect survival of neurons and glia, they are among the most commonly studied immune cells. However, the mechanisms that regulate myeloid cell activation and recruitment after SCI have not been adequately defined. In general, the dynamics and composition of myeloid cell recruitment to the injured spinal cord are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 111 publications
0
63
0
Order By: Relevance
“…This is due, in part, to the release of numerous mediators from microglia and macrophages that exert cytotoxic effects on CNS cells that can lead to demyelination and neuronal loss Hawthorne and Popovich 2011;Ren and Young 2013). Nevertheless, these cells also produce a variety of factors that promote cell survival and tissue healing, and under certain circumstances, may lead to protective effects in the injured CNS Popovich and Longbrake 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is due, in part, to the release of numerous mediators from microglia and macrophages that exert cytotoxic effects on CNS cells that can lead to demyelination and neuronal loss Hawthorne and Popovich 2011;Ren and Young 2013). Nevertheless, these cells also produce a variety of factors that promote cell survival and tissue healing, and under certain circumstances, may lead to protective effects in the injured CNS Popovich and Longbrake 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine gradients are argued to persist indefinitely or to reoccur periodically, in order to explain the observation of infiltrated for long periods, namely about 6 weeks for neutrophils and over 6 months for monocytes, in the lesioned spinal cord, despite their short lifespan of roughly 5 days and 2 months, respectively (Pillay et al 2010;Hawthorne and Popovich 2011). The rapid and transient induction of several chemokines, for example, CCL2, CCL21 and CXCL10, in neurons has recently been shown to precede the induction of these chemokines in astrocytes, although the latter are considered the major source of chemokines after CNS injury (de Haas et al 2007).…”
Section: Altered Chemokine Expression Following Cns Injurymentioning
confidence: 99%
“…In cases of MS or other demyelinating conditions, it has been shown that there exists a subset of microglia at the site of demyelination that can recruit oligodendrocyte precursor cells and phagocytose damaged neurons (Olah et al, 2011). In SCI, cells of the myeloid origin have been shown to play a role in intraspinal trafficking past the injury (Hawthorne and Popovich, 2011).…”
Section: Microglia In Disease and Agingmentioning
confidence: 99%